Dietary Patterns and Associated Microbiome Changes that Promote Oncogenesis - Ibragimova, Shakhzada; Ramachandran, Revathy; Ali, Fahad R.; Lipovich, Leonard; Ho, Samuel B. (Frontiers in Cell and Developmental Biology, 2021)
The recent increase in cancer incidences have been linked to lifestyle changes that result in obesity and metabolic syndrome. It is now evident that these trends are associated with the profound changes that occur in the intestinal microbiome, producing altered microbial population signatures that interact, directly or indirectly, with potentially pro-carcinogenic molecular pathways of transcription, proliferation, and inflammation. The effects of the entire gut microbial population on overall health are complex, but individual bacteria are known to play important and definable roles. Recent detailed examinations of a large number of subjects show a tight correlation between habitual diets, fecal microbiome signatures, and markers of metabolic health. Diets that score higher in healthfulness or diversity such as plant-based diets, have altered ratios of specific bacteria, including an increase in short chain fatty acid producers, which in turn have been linked to improved metabolic markers and lowered cancer risk. Contrarily, numerous studies have implicated less healthy, lower scoring diets such as the western diet with reduced intestinal epithelial defenses and promotion of specific bacteria that affect carcinogenic pathways. In this review, we will describe how different dietary patterns affect microbial populations in the gut and illustrate the subsequent impact of bacterial products and metabolites on molecular pathways of cancer development, both locally in the gut and systemically in distant organs.